Constitutive Modeling of Superplasticity Taking Account of Grain and Cavity Growth - TANAKA, Eiichi; ISHIKAWA, Hiroshi; MURAKAMI, Sumio (Transactions of the Japan Society of Mechanical Engineers Series A, 1997)
An inelastic constitutive model of superplasticity taking account of grain and cavity growth is formulated. We first assume that an inelastic strain rate is expressed as the sum of the term related to superplastic deformation mechanism and that related to ordinary deformation mechanism ; each term is represented by a viscoplastic model of the Chaboche type. Then the evolution of drag stress in the superplastic term is formulated by taking account of the effects of grain and cavity growth. Comparison of the predictions with monotonic tension experiments in literature shows that the proposed model can describe the typical deformation behavior of superplasticity such as the dependence of the slope of hardening curve on the strain-rate conditions, the dependence of flow stress on strain-rate history in the presence of static grain growth, and the softening of flow stress due to cavity growth.